2008
DOI: 10.3358/shokueishi.49.228
|View full text |Cite
|
Sign up to set email alerts
|

Multiresidue Method for Pesticides and Veterinary Drugs in Bovine Milk Using GC/MS and LC/MS/MS

Abstract: A simple, sensitive and selective method with gas chromatography/mass spectrometry (GC/ MS) and liquid chromatography/tandem mass spectrometry (LC/MS/MS) has been developed to detect 342 pesticides and veterinary drugs contaminating bovine milk at the maximum residue limits (MRLs) defined in the "positive list system". Sample preparation was performed by extracting the analytes with acetonitrile, followed by salting-out with sodium chloride. For some pesticides, the extract was further cleaned up by n-hexane p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Problems due to its complexity, together with the presence of interferents, make the analysis of this matrix difficult [8,9]. Although the number of publications on the determination of veterinary drugs in milk is extensive [10][11][12][13][14], the number of papers dedicated to pesticide residue analysis other than persistent organochlorines is relatively limited [15,16]. Hantash et al [15] described a method for the determination of carbaryl and its metabolite in complex matrices, using a molecularly imprinted polymer and LC-UV detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problems due to its complexity, together with the presence of interferents, make the analysis of this matrix difficult [8,9]. Although the number of publications on the determination of veterinary drugs in milk is extensive [10][11][12][13][14], the number of papers dedicated to pesticide residue analysis other than persistent organochlorines is relatively limited [15,16]. Hantash et al [15] described a method for the determination of carbaryl and its metabolite in complex matrices, using a molecularly imprinted polymer and LC-UV detection.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers appeared on the simultaneous determination of organochlorine and other groups of pesticides (pyrethroids by SPE and GC with microelectron-capture detection (GC-mu ECD) [17] or organophosphorus by GC with MS/MS [18]). Only one paper was specifically dedicated to detect 342 pesticides and veterinary drugs contaminating bovine milk by GC-MS and LC-MS/MS [19]. Generally, the methods described are based on two different strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Saito et al reported using GC-MS and LC-MS/MS to detect several hundred rodenticides and pesticides in bovine milk. 24 Compounds were extracted in acetonitrile and salted out using sodium chloride. In some cases, an additional step of n-hexane partitioning and PSA cartridge column 13 chromatograph was used.…”
Section: Toxic Chemical Analysis In Foodmentioning
confidence: 99%
“…Analytical methods, including gas chromatography (GC) (Song & McNair, 2002), GS/ mass spectrometry (MS) (Carabias-Martinez, Garcia-Hermida, Rodriguez-Gonzalo, & Ruano-Miguel, 2005;Saito et al, 2008), high-performance liquid chromatography (HPLC)/MS (Kruve, Kuennapas, Herodes, & Leito, 2008;Nunes, Alonso, Ribeiro, & Barcelo, 2000;Yang, Li, Miao, Zhao, & Wu, 2014;Yuan, Xiong, Li, Chen, & Liu, 2011), liquid chromatography-tandem MS (LC-MS/MS) (Franca, Brandao, Sodre, & Caldas, 2015;Huang et al, 2009), and enzyme-linked immunosorbent assays (ELISAs) (Rodolico, Giovinazzo, & Mosconi, 1997) have been already used for the environmental analysis of ALD. The GC and HPLC methods have disadvantages insofar as they are complex, time consuming, and labor intensive.…”
Section: Introductionmentioning
confidence: 99%